STRATEGI KOMUNIKASI BADAN PEMBINAAN HUKUM NASIONAL (BPHN) DALAM MELAKUKAN SOSIALISASI DI MASA PANDEMIC COVID-19 - Lifia Nifri Azkia; Shilvy Andini Sunarto; Widiastiana Vista Wijaya; Citra Puspa Maulidina (Asosiasi Dosen Muda Indonesia, 2023)
The purpose of this study is to find out how the Communication Strategy of the National Legal Development Agency (BPHN) supports and hinders the implementation of legal socialization through online media. The method used is qualitative with interviews. The informants in this study were Mr. Gunawan as the Coordinator of the Legal Cultivation Division of the BPHN Center, Mrs. Asiyah Budiarti as BPHN Junior Expert Legal Counselor and Mr. Ahmad Noval as a private employee. Using the theory of diffusion of innovation. The results of this study BPHN in developing a communication strategy in legal outreach during the Covid-19 Pandemic used two methods, namely direct legal counseling by going directly to the field assisted by obligatory parties, then using the indirect method by strengthening BPHN's social media such as Instagram, YouTube, websites containing legal content.